Left ventricular assessment in patients with significant mitral incompetence: a multi-modality imaging study - Elgammal, Reham Mostafa; Elsaiedy, Mona Adel; Alamrosy, Mahmoud Zki; Elsetiha, Mohamed Elsaied; Almasry, Magdy Mohamed (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: Detection of the deleterious effect of MR on LV is crucial in guiding the surgical decision. Aim of the study: Comprehensive assessment of LV with significant primary MR using (2D, 3D echo and CMR). Methods: 40 patients with significant MR have been recruited in a prospective study. Patients underwent 2D and 3D echo and CMR studies. LV volumes, function and GLS were calculated. Results: End diastolic and systolic volumes were significantly larger when measured by CMR (all p < 0.001). EDV measures were strongly correlated with CMR and 3D echocardiography. Conclusion: It’s important to identify early deleterious LV changes.